Toll-Like Receptor-Mediated Activation of CD39 Internalization in BMDCs Leads to Extracellular ATP Accumulation and Facilitates P2X7 Receptor Activation - Zhao, Ronglan; Qiao, Jinjuan; Zhang, Xumei; Zhao, Yansong; Meng, Xiangying; Sun, Deming; Peng, Xiaoxiang (Frontiers in Immunology, 2019)
Toll-like receptors (TLRs) trigger innate immune responses through their recognition of conserved molecular ligands of either endogenous or microbial origin. Although activation, function and signaling pathways of TLRs were already well studied, their precise function in specific cell types, especially innate immune cells, needs to be further clarified. In this study, we showed that when significantly decreased amounts of membrane CD39, an ATP-degrading enzyme, were detected in lipopolysaccharide (LPS)-treated bone marrow-derived DCs (BMDCs), Cd39 mRNA expression and whole-cell CD39 expression were at the same levels as those in untreated BMDCs. Further experiments demonstrated that the downregulation of membrane CD39 expression in LPS-treated BMDCs was mediated by endocytosis leading to membrane-exposed CD39 downregulation, which was positively associated with decreased enzymatic activity in ATP metabolism and increased extracellular ATP accumulation. The accumulated ATP promoted intracellular calcium accumulation and IL-1β production in BMDCs through P2X7 signaling activation. Further research revealed that not only LPS but also other TLR ligands, excluding polyI:C, induced CD39 internalization in BMDCs and that the MyD88 pathway was critical in this process. The results suggested that the activation of CD39 internalization in DCs induced by a TLR ligand caused increased ATP accumulation, leading to P2X7 receptor activation that mediated a proinflammatory effect. Considering the strong modulatory effect of extracellular ATP accumulation on the immune response and inflammation, the manipulation of membrane CD39 expression on DCs may have implications on the regulation and treatment of inflammatory responses.